Self-Control Therapy: Daily Accounting and Focus Group Discussions Reduce Consumptive Behavior of E-Money Use in Millennials - Pratika, Netty Dyan; Manikotama, Annisa; Pratiwi, Dinda Hana; Wahyuningdias, Khofifah (Budapest International Research and Critics University, 2021)
This study aims to find out if there are differences in the level of consumptive behavior after being given treatment in the form of self-control therapy with daily accounting methods and focus group discussions. The study uses an experimental quantitative approach. The subjects of this study were 33 Mulawarman University students who were active users of e-money who were selected using purposive sampling techniques. The data collection method used is the scale of consumptive behavior. The collected data is analyzed with the Different Test method, the Wilcoxon Test with the help of SPSS software version 22. The results of this study showed that the pre-test of consumptive behavior scale with post-test consumptive behavior scale showed a P value of 0,000 < 0.05 which means that there was a decrease in consumptive behavior after being treated in the form of daily accounting and focus group discussion then on follow-up the consumer behavior scale showed a P value of 0.694 > 0.05 which means not There’s a significant difference.